Floristic and taxonomic aspects of mosses from Barcarena, Pará - Souza, Adriana Paula da Silva; Lisboa, Regina Célia Lobato (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
The municipality of Barcarena, Pará is placed at 30 km from Belém city. It has an area of 1.316,2 km2, in great part limited by Marajó Bay. Forty-three species of mosses, belonging to 13 families, were found. It also includes data on basyonym, type locality, geographic distribution in Brazil, habitat and comments about the morphology of species, and quotations of descriptions and illustrations in literature. Isopterygium acutifolium Ireland is the new occurrence, and it’s illustrated here.
Keywords: Bryoflora; Amazon vegetation; Isopterygium acutifolium Ireland